ICPSR Data Holdings 2005
DOI: 10.3886/icpsr01313
|View full text |Cite
|
Sign up to set email alerts
|

Controlling for Heterogeneity in Gravity Models of Trade and Integration

Abstract: Distance, expressed in kilometers, is the great circle distance between geographic centers, using the Haversine formula. Coordinates from the CIA's The World Factbook 2000. Contiguity is equal to 1 if two trading partners share a border. From the CIA's The World Factbook 2000. Common Language is equal to 1 if two trading partners share a common first language. From the CIA's The World Factbook 2000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
195
0
12

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(208 citation statements)
references
References 12 publications
1
195
0
12
Order By: Relevance
“…Os coeficientes de determinação obtidos nos ajustes para expotação de celulose e de papel se apresentaram ligeiramente acima de 60%, que é um desempenho aceitável em estudos com modelo gravitacional (CHENG; WALL, 1999;FEENSTRA et al, 2001;BAIER;BERGSTRAND, 2009).…”
Section: Discussionunclassified
“…Os coeficientes de determinação obtidos nos ajustes para expotação de celulose e de papel se apresentaram ligeiramente acima de 60%, que é um desempenho aceitável em estudos com modelo gravitacional (CHENG; WALL, 1999;FEENSTRA et al, 2001;BAIER;BERGSTRAND, 2009).…”
Section: Discussionunclassified
“…The heterogeneity is caused by differences in the individual preferences, endowments, and attributes. Researchers have suggested that the FEM and the random effect model (REM) be used to deal with this problem (Egger 2000;Egger and Pfaffermayr 2003;Cheng and Wall 2005;De Benedictis and Vicarelli 2005). While both models can be used to control for the unobserved heterogeneity, they differ in approach.…”
Section: Model Estimation and Resultsmentioning
confidence: 99%
“…Various panel data techniques are used in the literature to estimate the gravity model. Many of them used within-group estimator for one-way or two-way fixed effects (FE) model, error components generalised least square estimator (EC-GLS) for random effects (RE) model, Hausman-Taylor instrumental variable method (Egger 2002;Cheng -Wall 2005;SerlengaShin 2007;Bussiere et al 2008). Furthermore, the Poisson fixed effects method and the Poisson pseudo-maximum likelihood method have been used as solutions for zero trade flows problem (for instance, Silva -Tenreyro 2006, or Westerlund -Wilhelmsson 2011.…”
Section: Model Data and Methodologymentioning
confidence: 99%